2012
DOI: 10.1177/0003319712440619
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Levels and the Burden of Coronary Atherosclerosis in Patients With STEMI

Abstract: We investigated whether serum bilirubin level (a marker of heme oxygenase activity) is a predictor of high levels of SYNTAX score (SXscore) in patients with acute myocardial infarction. Patients (n = 281; male 77%; mean age 60 ± 12) who were admitted with ST-elevation myocardial infarctions (STEMIs) were enrolled. Patients were divided into 2 groups. Group 1 was defined as SXscore <22 and group 2 was defined as SXscore ≥22. Total bilirubin levels were significantly higher in the high-SXscore group than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
4
34
0
1
Order By: Relevance
“…The heme oxygenase (HO) enzyme that is responsible for the degradation of heme groups in the metabolism of bilirubin is a stress-inducible enzyme and has antioxidative features [4]. There are 2 isozymes of this enzyme, HO-1 and HO-2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The heme oxygenase (HO) enzyme that is responsible for the degradation of heme groups in the metabolism of bilirubin is a stress-inducible enzyme and has antioxidative features [4]. There are 2 isozymes of this enzyme, HO-1 and HO-2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…21 Such an association between higher serum TB and higher SYNTAX score was also found in patients with STEMI. 22 Increasing TB was significantly associated with the risk of pump failure death but not for sudden death in patients with severe systolic heart failure. 11 HO-1 protein and HO activity are markedly upregulated in the myocardium in response to infarction and pressure overload in animals.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that the prognostic significance of TB is different in stable CAD and acute myocardial infarction (AMI) (Huang et al, 2017). For stable CAD, elevated TB levels are associated with better prognosis through reduction of cardiac reperfusion injury and improvement of postischemic cardiac function (Bakrania et al, 2017;Clark et al, 2000), while in AMI patients, elevated TB levels correlated with high burden thrombus (Hamur et al, 2016), coronary atherosclerosis (Sahin et al, 2013), and angiographic no-flow (Celik et al, 2014). The activity of myocardial heme oxygenase-1 (HO-1) increased significantly in response to acute infarction, and therefore, elevated TB levels represent stress-induced HO-1 activation in AMI patients (Okuhara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%